2021
DOI: 10.3390/ph14040314
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-100 Mediates Hydrogen Peroxide-Induced Apoptosis of Human Retinal Pigment Epithelium ARPE-19 Cells

Abstract: This study investigated the regulatory role of microRNA 100 (miR-100) in hydrogen peroxide (H2O2)-induced apoptosis of human retinal pigment epithelial ARPE-19 cells. H2O2 induced oxidative cell death of cultured ARPE-19 cells was measured by cytotoxicity assay. qRT-PCR was used to quantify cytosolic and extracellular contents of miR-100. Kinase and miR-100 inhibition treatments were applied to determine the regulatory signaling pathways involved in cell death regulation. H2O2 dose-dependently reduced viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In AMD disease, RPE cells may experience oxidative stress-induced senescence. Whereas oxidative stress products such as H 2 O 2 attack DNA, proteins, lipids, and other cellular components indiscriminately and plays an important role in controlling cellular functions such as cell differentiation, proliferation, migration, apoptosis, and death (4,5) MicroRNA (miRNA) can inhibit endogenous gene expression by translationally cleaving gene transcripts (9). It can regulate the biological functions of cells by targeting several downstream genes, thus playing an important regulatory role in various diseases, including AMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In AMD disease, RPE cells may experience oxidative stress-induced senescence. Whereas oxidative stress products such as H 2 O 2 attack DNA, proteins, lipids, and other cellular components indiscriminately and plays an important role in controlling cellular functions such as cell differentiation, proliferation, migration, apoptosis, and death (4,5) MicroRNA (miRNA) can inhibit endogenous gene expression by translationally cleaving gene transcripts (9). It can regulate the biological functions of cells by targeting several downstream genes, thus playing an important regulatory role in various diseases, including AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of let-7b, let-7a, miR-125b, miR-24, miR-320, miR-23b, let-7e, and let-7d miRNAs in ROS-accumulating ARPE-19 cells was determined by microarray hybridization analysis, which caused apoptosis and resulted in an increase in the expression of the target genes HMOX1 and GADD153 (13). It has also been shown that treatment with miR-100 antagomir prevented excessive oxidation-induced cell death in ARPE-19 cells and exerts a protective effect on oxidative cell death (5).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The activation of the apoptosis signal-regulating kinase 1 (ASK-1)/p38 mitogen-activated protein kinase (MAPK)/JNK/extracellular-signal-regulated kinase (ERK) axis by ROS can lead to caspase-3 activation and cellular membrane disassembly, promoting cell death [ 99 , 100 ]. Chronic exposure to ROS can activate the phosphoinositide 3-kinase (PI3K)/Akt axis while attenuating the mammalian target of rapamycin (mTOR) pathway, further stimulating the NF-kB and enhancing inflammatory events [ 101 ]. Additionally, excessive ROS disrupts glutamate metabolism, leading to the neurotoxic extracellular accumulation of glutamate, as dysfunctional glial cells fail to properly buffer the excess glutamate [ 16 , 102 , 103 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…This axis triggers the mitochondrial apoptotic pathway, characterized by the release of the Bcl-2 associated X-protein (Bax) and cytochrome c into the cytosol, followed by apoptosome formation (cytochrome c/apoptotic protease-activating factor 1(Apaf-1)/caspase-9), ultimately leading to caspase-3 activation [220,222,223]. Moreover, hydrogen peroxide has been described to activate the phosphoinositide 3-kinase (PI3K)/ Ak strain transforming (Akt) axis and reduce the intracellular concentration of the mammalian target of rapamycin (mTor), promoting NF-kB activation [224].…”
Section: Oxidative Stress In the Pathogenesis Of Glaucomamentioning
confidence: 99%